Impact of Interferon Lambda 4 Genotype on Interferon‐Stimulated Gene Expression During Direct‐Acting Antiviral Therapy for Hepatitis C. Issue 3 (15th September 2018) - Ramamurthy, Narayan; Marchi, Emanuele; Ansari, M. Azim; Pedergnana, Vincent; Mclean, Angela; Hudson, Emma; ,; Bowden, Rory; Spencer, Chris C.A.; Barnes, Eleanor; Klenerman, Paul
Abstract : New directly acting antivirals (DAAs) provide very high cure rates in most patients infected by hepatitis C virus (HCV). However, some patient groups have been relatively harder to treat, including those with cirrhosis or infected with HCV genotype 3. In the recent BOSON trial, genotype 3, patients with cirrhosis receiving a 16‐week course of sofosbuvir and ribavirin had a sustained virological response (SVR) rate of around 50%. In patients with cirrhosis, interferon lambda 4 ( IFNL4 ) CC genotype was significantly associated with SVR. This genotype was also associated with a lower interferon‐stimulated gene (ISG) signature in peripheral blood and in liver at baseline. Unexpectedly, patients with the CC genotype showed a dynamic increase in ISG expression between weeks 4 and 16 of DAA therapy, whereas the reverse was true for non‐CC patients. Conclusion: These data provide an important dynamic link between host genotype and phenotype in HCV therapy also potentially relevant to naturally acquired infection. (Hepatology 2018; 00:000‐000).